The Potential for Cellular Therapy Combined with Growth Factors in Spinal Cord Injury - Jack Rosner; Pablo Avalos; Frank Acosta; John Liu; Doniel Drazin (Stem Cells International)
Any traumatic spinal cord injury (SCI) may cause symptoms ranging from pain to complete loss of motor and sensory functions below the level of the injury. Currently, there are over 2 million SCI patients worldwide. The cost of their necessary continuing care creates a burden for the patient, their families, and society. Presently, few SCI treatments are available and none have facilitated neural regeneration and/or significant functional improvement. Research is being conducted in the following areas: pathophysiology, cellular therapies (Schwann cells, embryonic stem cells, induced pluripotent stem cells, mesenchymal stem cells, olfactory ensheathing cells), growth factors (BDNF), inhibitory molecules (NG2, myelin protein), and combination therapies (cell grafts and neurotrophins, cotransplantation). Results are often limited because of the inhibitory environment created following the injury and the limited regenerative potential of the central nervous system. Therapies that show promise in small animal models may not transfer to nonhuman primates and humans. None of the research has resulted in remarkable improvement, but many areas show promise. Studies have suggested that a combination of therapies may enhance results and may be more effective than a single therapy. This paper reviews and discusses the most promising new SCI research including combination therapies.